2009
DOI: 10.1124/jpet.109.152835
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin Improves and Prevents Trinitrobenzene Sulfonic Acid-Induced Colitis in Mice

Abstract: Inflammatory bowel disease (IBD) is chronic inflammatory and relapsing disease of the gut. It has been known that activation of nuclear factor-B (NF-B) and production of proinflammatory cytokines play important roles in the pathogenesis of IBD. In this study, the effect of vanillin (4-hydroxy-3-methoxybenzaldehyde), a potent nuclear factor-B (NF-B) inhibitor, was evaluated in mice with trinitrobenzene sulfonic acid (TNBS)-induced colitis. Oral administration of vanillin improved macroscopic and histological fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 39 publications
1
65
0
1
Order By: Relevance
“…Recently, it was reported that vanillin exerts an anti-inflammatory activity in ICR mice, and the authors suggested that this is due to the release of inflammatory mediators being blocked during the first stage (72). A subsequent study further demonstrated the anti-inflammatory effect of vanillin during a treatment of inflammatory bowel diseases where vanillin prevented trinitrobenzene sulfonic acid-induced colitis and reduced established colitis in mice (73). Finally, vanillin decreased angiogenesis and showed protected against hepatocarcinogenesis (74), while also displaying anti-cancer properties as evidenced by its inhibition of matrix metalloproteinase-9 and P13K gene expression levels and regulation of the cell cycle and apoptosis in HepG2 cells, through which it suppressed the invasion and migration of cancer cells (66,75,76).…”
Section: Phenolic Aldehydes Resulting From Lignin Hydrolysismentioning
confidence: 88%
“…Recently, it was reported that vanillin exerts an anti-inflammatory activity in ICR mice, and the authors suggested that this is due to the release of inflammatory mediators being blocked during the first stage (72). A subsequent study further demonstrated the anti-inflammatory effect of vanillin during a treatment of inflammatory bowel diseases where vanillin prevented trinitrobenzene sulfonic acid-induced colitis and reduced established colitis in mice (73). Finally, vanillin decreased angiogenesis and showed protected against hepatocarcinogenesis (74), while also displaying anti-cancer properties as evidenced by its inhibition of matrix metalloproteinase-9 and P13K gene expression levels and regulation of the cell cycle and apoptosis in HepG2 cells, through which it suppressed the invasion and migration of cancer cells (66,75,76).…”
Section: Phenolic Aldehydes Resulting From Lignin Hydrolysismentioning
confidence: 88%
“…However, with improvement of the patient's condition, these parameters of oxidative stress go back to normal levels (178). As NF-B is a major inducer of inflammatory cytokines, the effect of a potent NF-B inhibitor, vanillin, has been studied in mouse model of colitis (325). Vanillin was shown to suppress the production of Th1 cytokines as well as scavenges 1 O 2 , underscoring its potential as a future treatment for IBD.…”
Section: Ibds (Ulcerative Colitis Crohn's Disease)mentioning
confidence: 99%
“…Vanillin has been reported to exhibit multifunctional effects, including antimutagenic, [13][14][15] antiangiogenetic, 16) anti-colitis, 17) anti-sickling, 18) and antianalgesic effects. 19) Recently, we proposed the addition of antioxidant capacity to the multifunctionality of vanillin, 20) but the pharmacological action of ethyl vanillin has been little reported.…”
Section: Contents Of Ethyl Vanillin-and Vanillin-related Compounds Anmentioning
confidence: 99%